2016
DOI: 10.1088/0031-9155/61/14/5149
|View full text |Cite
|
Sign up to set email alerts
|

Performance of MACACO Compton telescope for ion-beam therapy monitoring: first test with proton beams

Abstract: In order to exploit the advantages of ion-beam therapy in a clinical setting, delivery verification techniques are necessary to detect deviations from the planned treatment. Efforts are currently oriented towards the development of devices for real-time range monitoring. Among the different detector concepts proposed, Compton cameras are employed to detect prompt gammas and represent a valid candidate for real-time range verification. We present the first on-beam test of MACACO, a Compton telescope (multi-laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 32 publications
0
38
0
Order By: Relevance
“…In fact, each element in tissue emits a unique spectrum of PGs during proton irradiation 135137 . In addition to the already reported use of the best emission lines for range verification 74,76, 87, 89, 111,113 , it has also been shown that the total emission from oxygen per unit dose is directly proportional to the concentration of oxygen within a proton beam irradiated volume of tissue 138 . This observation led to suggestions that if PG emissions from several key elements in tissue (O, C, N, Ca, etc.)…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In fact, each element in tissue emits a unique spectrum of PGs during proton irradiation 135137 . In addition to the already reported use of the best emission lines for range verification 74,76, 87, 89, 111,113 , it has also been shown that the total emission from oxygen per unit dose is directly proportional to the concentration of oxygen within a proton beam irradiated volume of tissue 138 . This observation led to suggestions that if PG emissions from several key elements in tissue (O, C, N, Ca, etc.)…”
Section: Discussionmentioning
confidence: 90%
“…Several prototype CCs have been constructed and tested in clinical proton therapy environments 110113 . As shown in Figure 8, one such design currently being tested consists of a two-stage CC mounted on the underside of the treatment couch.…”
Section: General Purpose Techniquesmentioning
confidence: 99%
“…Since the Compton camera (CC) was first proposed for medical imaging (Todd et al , 1974), many researchers have studied its use for a wide range of medical applications, including 2D and 3D imaging of prompt gamma (PG) emission from a patient during proton radiotherapy as a means of providing in vivo verification of the delivered proton beam range (Frandes et al , 2010; Gillam et al , 2011; Golnik et al , 2016; Hueso-Gonzalez et al , 2016; Kim et al , 2013; Kormoll et al , 2011; Krimmer et al , 2015; Llosa et al , 2012; Lojacono et al , 2013; McCleskey et al , 2015; Munoz et al , 2017; Peterson et al , 2010; Polf et al , 2015; Richard et al , 2011; Robertson et al , 2011; Roellinghoff et al , 2014; Rohling et al , 2017; Seo et al , 2010; Solevi et al , 2016; Thirolf et al , 2016; Thirolf et al , 2014). In standard Compton imaging, information pertaining to the energy deposited by and spatial coordinates of gammas that interact at least twice in the stages of a CC is used to create the images.…”
Section: Introductionmentioning
confidence: 99%
“…In addition pair production events, and gammas that Compton scatter twice, but do not deposit their total energy (Hueso-Gonzalez et al , 2017; Ortega et al , 2015; Rohling et al , 2017) also effect the imaging capabilities of the CC. These events greatly increase image noise and reduce the achievable spatial resolution of PG imaging (Ortega et al , 2015; Solevi et al , 2016). One technique researchers have studied to remove and reduce the effects of these “bad scatter events” is by limiting the initial PG energy range to > 2 MeV (Polf et al , 2009b; Rohling et al , 2017) or to an energy window around a specific PG emission lines (Hilaire et al , 2016; Hueso-Gonzalez et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It also adds uncertainty because of the need to correlate the proton transit time with a spatial location in the patient. Finally, the application of Compton cameras is being investigated (Hueso-González et al 2017; Solevi et al 2016; Aldawood et al 2017; Rohling et al 2017; Draeger et al 2018). These systems do not require physical collimation either, but rely on the detection of multiple Compton scatter interactions per incident gamma-ray in order to reconstruct its origin region.…”
Section: Introductionmentioning
confidence: 99%